Effect of realistic ballasted track in the underbody flow of a high-speed train via CFD simulations. Issue 184 (January 2019) - Paz, C.; Suárez, E.; Gil, C.; Cabarcos, A.
Abstract: The underbody flow of high-speed trains is a matter of concern in the railway industry because of its relation to the ballast flight phenomenon, and several experimental campaigns are focused on evaluating its characteristics. Computational simulations are considered as a flexible and economical alternative. However, the aforementioned simulations include only simplified track models with a flat ground that do not include the sleepers or the profiles of stones. The present study uses a previously developed methodology to reproduce the passing of a high-speed train over a scanned real profile of stones and sleepers and determines the effect on the surrounding flow and compares the results relative to those of a flat ballast bed. The simulations are validated relative to experimental data published in the bibliography with satisfactory results. The results confirm expected differences between flat and rough configurations, thereby revealing a more chaotic velocity field near the rough ballast and the presence of a larger number and smaller size of turbulence structures. The rough configuration also allows for the measurement of the pressure on the surface of the stones and the application of a predictive model for ballast flight. The obtained results are similar to those in experimental tests. Highlights: An innovative CFD methodogy for the simulation of high-speed trains is proposed. A reallistic ballast profile from in situ scan measurements was included in the CFD model. This methodology allows to reproduce the passing of a high-speed train over a real profile. Validation against previous experimental results from literatura was done. Differences in velocity and turbulence flows were revealed when compared with flat bed results.